Bivariate mean value interpolation on circles - K. R. Fard (Հայաստանի ԳԱԱ)
In this paper we prove that the bivariate mean-value interpolation problem, where part of the interpolation parameters are integrals over concentric circles is not poised.
Keywords: Mathematics; Science